A Nile Red-assisted colorimetric and SERS dual-mode strategy for the rapid and highly sensitive detection of nanoplastics - Zhaoyan Yang; Gujie Pei; Jinlin Zhang; Bing Chen; Yeming Qing; Kuo Yang; Dan Zhu; Bingxiang Li; Zhuyuan Wang (Analytica Chimica Acta, 2026)

First record of Fraxinoxylon (Oleaceae) from the Miocene of Sihong, Jiangsu Province, China, and its palaeogeographic implication - Yanbin Zhu; Ya Li; Xiaohua Zhou; Yanfeng Song; Kai Liu; Ren Jiang; Yeming Cheng (Review of Palaeobotany and Palynology, 2026)

Physicochemical properties and flavor profile of coconut yoghurt: the dual role of fat reduction and protein fortification - Jiawei Dai; Ruoyu Xing; Yuqing Wang; Caimeng Zhang; Yufei Hua; Yeming Chen; Xingfei Li; Xiangzhen Kong (Food Research International, 2026)

Mild heating modification of disulfide bond-linked protein aggregates and the green process for the preparation of soybean globulins - Longzheng Zhou; Xiaoxiao Feng; Xingfei Li; Xiangzhen Kong; Yeming Chen; Caimeng Zhang; Yufei Hua (Food Research International, 2025)

GC×GC-TOFMS and LC-ESI-MS/MS based flavoromics and metabolomics studies on the lactic acid bacteria fermentation of soymilks with dairy milk as the reference - Gaiwen Yu; Caimeng Zhang; Xingfei Li; Xiangzhen Kong; Yeming Chen; Yufei Hua (Food Bioscience, 2025)

A wash-free red fluorescent probe for real-time monitoring of mitochondrial viscosity changes and tumor imaging - Kun Yu; Yeming Zhang; Yuqing Wang; Jiale Li; Jie Wang; Sichen Zhang; Aobo Sun; Xue Zhang; Lei Hu; Hui Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Biotransformation of important soymilk off-flavor components during lactic acid bacteria fermentation: screening and quantitative analysis of volatile organic compounds - Gaiwen Yu; Caimeng Zhang; Xingfei Li; Xiangzhen Kong; Yeming Chen; Yufei Hua (Food Bioscience, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Multi-objective evolutionary neural architecture search for network intrusion detection - Qiuzhen Lin; Zhihao Liu; Yeming Yang; Ka-Chun Wong; Yahui Lu; Jianqiang Li (Swarm and Evolutionary Computation, 2024)

In vitro protein digestive properties and peptidomic characterization of five whole component plant protein beverages using a pepsin-pancreatin model - Junna Zhao; Xiangzhen Kong; Caimeng Zhang; Yufei Hua; Yeming Chen; Xingfei Li (Food Research International, 2024)

PM2.5 induces developmental neurotoxicity in cortical organoids - Yuqing Han; Zhenjie Yu; Yue Chen; Xiaoyu Guo; Yeming Liu; Hao Zhang; Zhiqing Li; Liqun Chen (Environmental Pollution, 2024)

Geological investigation of the lunar Apollo basin: From surface composition to interior structure - Dijun Guo; Yeming Bao; Yang Liu; Xing Wu; Yuchen Xu; Yazhou Yang; Feng Zhang; Bradley Jolliff; Shuai Li; Zhenxing Zhao; Liying Huang; Jianzhong Liu; et al. (Earth and Planetary Science Letters, 2024)

Fine particulate matter concentration prediction based on hybrid convolutional network with aggregated local and global spatiotemporal information: A case study in Beijing and Chongqing - Qiaolin Zeng; Yang Cao; Meng Fan; Liangfu Chen; Hao Zhu; Lihui Wang; Yeming Li; Sizhu Liu (Atmospheric Environment, 2024)

Conversion of pure Chinese fir plantation to multi-layered mixed plantation increases organic phosphorus accumulation and transformation within soil aggregates - Haimei Huang; Xueman Huang; Yi Wang; Jiajun Li; Mingzhu Xiang; Changhang Li; Shushou Liao; Yeming You (Applied Soil Ecology, 2024)

Low-calorie bulk sweeteners: Recent advances in physical benefits, applications, and bioproduction - Jin Li; Quanyu Dai; Yingying Zhu; Wei Xu; Wenli Zhang; Yeming Chen; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Multi-agent deep Q-network-based metaheuristic algorithm for Nurse Rostering Problem - Xinzhi Zhang; Yeming Yang; Qingling Zhu; Qiuzhen Lin; Weineng Chen; Jianqiang Li; Carlos A. Coello Coello (Swarm and Evolutionary Computation, 2024)

Overview of vegetation factors related to the diversity of arbuscular mycorrhizal fungi and their interactions in karst areas - Ying Li; Zhongfeng Zhang; Shuhui Tan; Limin Yu; ChunGui Tang; Yeming You (Applied Soil Ecology, 2024)

Acid induced gelation of heated soymilks: Protein structure, molecular interactions and gel properties - Qianru Li; Yufei Hua; Xingfei Li; Xiangzhen Kong; Caimeng Zhang; Yeming Chen (Food Hydrocolloids, 2024)

Stability Analysis and Deformation Control of Tunnel with Extremely Weak Surrounding Rocks Caused by Strike-Slip Fault Activity - Ziquan Chen; Qixiang Yan; Zihan Zhou; Chuan He; Tiansheng Li; Yeming Bao (Rock Mechanics and Rock Engineering, 2023)

Estimation of ground-level O3 concentration in the Yangtze River Delta region based on a high-performance spatiotemporal model MixNet - Qiaolin Zeng; Yechen Wang; Jinhua Tao; Meng Fan; Songyan Zhu; Liangfu Chen; Lihui Wang; Yeming Li (Science of The Total Environment, 2023)

Full-coverage estimation of PM2.5 in the Beijing-Tianjin-Hebei region by using a two-stage model - Qiaolin Zeng; Yeming Li; Jinhua Tao; Meng Fan; Liangfu Chen; Lihui Wang; Yechen Wang (Atmospheric Environment, 2023)

Comparison of physicochemical properties and volatile flavor compounds of plant-based yoghurt and dairy yoghurt - Xinlu Wang; Xiangzhen Kong; Caimeng Zhang; Yufei Hua; Yeming Chen; Xingfei Li (Food Research International, 2023)

Growing of fungi on the stored low denatured defatted soybean meals and the hydrolysis of proteins and isoflavone glycosides by fungal enzymes - Xiaoxu Zhu; Yufei Hua; Xingfei Li; Xiangzhen Kong; Yeming Chen; Caimeng Zhang (Food Research International, 2023)

Phenolic compounds in walnut pellicle improve walnut (Juglans regia L.) protein solubility under pH-shifting condition - Xiangzhen Kong; Zilin Huang; Caimeng Zhang; Yufei Hua; Yeming Chen; Xingfei Li (Food Research International, 2023)

The ER membrane protein complex subunit Emc3 controls angiogenesis via the FZD4/WNT signaling axis - Mu Yang; Shujin Li; Wenjing Liu; Xiao Li; Yunqi He; Yeming Yang; Kuanxiang Sun; Lin Zhang; Wanli Tian; Lixin Duan; Huafu Chen; Dezhong Yao; et al. (Science China Life Sciences, 2021)

Mfge8 attenuates human gastric antrum smooth muscle contractions - Wen Li; Ashley Olseen; Yeming Xie; Cristina Alexandru; Andrew Outland; Angela F. Herrera; Andrew J. Syder; Jill Wykosky; Brian A. Perrino (Journal of Muscle Research and Cell Motility, 2021)
Coordinated gastric smooth muscle contraction is critical for proper digestion and is adversely affected by a number of gastric motility disorders. In this study we report that the secreted protein Mfge8 (milk fat globule-EGF factor 8) inhibits the contractile responses of human gastric antrum muscles to cholinergic stimuli by reducing the inhibitory phosphorylation of the MYPT1 (myosin phosphatase-targeting subunit (1) subunit of MLCP (myosin light chain phosphatase), resulting in reduced LC20 (smooth muscle myosin regulatory light chain (2) phosphorylation. Mfge8 reduced the agonist-induced increase in the F-actin/G-actin ratios of β-actin and γ-actin1. We show that endogenous Mfge8 is bound to its receptor, α8β1 integrin, in human gastric antrum muscles, suggesting that human gastric antrum muscle mechanical responses are regulated by Mfge8. The regulation of gastric antrum smooth muscles by Mfge8 and α8 integrin functions as a brake on gastric antrum mechanical activities. Further studies of the role of Mfge8 and α8 integrin in regulating gastric antrum function will likely reveal additional novel aspects of gastric smooth muscle motility mechanisms.

Optimal rotation length for carbon sequestration in Eucalyptus plantations in subtropical China - Xiaoguo Zhou; Yuanguang Wen; Uromi Manage Goodale; Hua Zuo; Hongguang Zhu; Xiaoqiong Li; Yeming You; Li Yan; Yong Su; Xueman Huang (New Forests, 2017)

Pliocene charcoals from Shanxi Province of China and their application to studies of prehistoric wildfires - YeMing Cheng; XiaoMei Jiang; ChengSen Li; YuFei Wang (Science China Earth Sciences, 2011)

Expression of Human Calcitonin by Microencapsulated Recombinant Myoblasts - Yeming Wang; Bingfang Zeng; Xiaolin Li (Biotechnology Letters, 2006)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.